Penegakan Hukum atas Kejahatan Siber Bermodus Pesan Whatsapp dalam Sektor Perbankan - I Gede Krisna Dana Yasa; Johannes Ibrahim Kosasih; I Made Aditya Mantara Putra (Verdict: Journal of Law Science, 2026)
The rapid advancement of digital information and communication technology has significantly transformed banking services by enabling customers to conduct financial transactions through electronic platforms with greater efficiency, accessibility, and convenience. Despite these benefits, technological developments have also created opportunities for cybercrime, particularly through the misuse of WhatsApp as a medium for fraudulent activities targeting banking customers. This phenomenon raises important legal issues concerning the regulatory framework governing digital communication via WhatsApp and the effectiveness of law enforcement mechanisms in addressing cybercrime that results in financial losses for banking customers. Accordingly, this study examines two principal issues: (1) the legal regulation governing the use of WhatsApp digital messaging in relation to cybercrime within the banking sector; and (2) the implementation of law enforcement against perpetrators of WhatsApp-based cybercrime that causes customer losses. This research employs a normative legal method using statutory and conceptual approaches to analyze relevant legal principles and regulations. The findings demonstrate that the legal framework governing cybercrime is primarily established under the Law on Electronic Information and Transactions, the Personal Data Protection Law, the Indonesian Criminal Code, and various regulations concerning the banking sector. Law enforcement is implemented through the imposition of criminal penalties and monetary fines aimed at providing legal certainty and deterrence. Nevertheless, the effectiveness of law enforcement remains constrained by several challenges, including limited public awareness of cyber threats, technological limitations in digital investigations, and difficulties in identifying and prosecuting cybercrime perpetrators operating through electronic communication platforms.